Answer:
![x=(1)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g646m842xo2rto0iqy30ez7q4ddo1pfooi.png)
Explanation:
We can use some logarithmic rules to solve this easily.
Note: Ln means
![Log_e](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jnvari85l1um37hgyfax3b1953uke4172o.png)
Now, lets start with the equation:
![ln(2x) + ln(2) = 0\\ln(2x) = -ln(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7agnlvgwkh5jxlthgu8uocthn2sbxzmizz.png)
Writing left side with logarithmic base e, we have:
![Log_(e)(2x) = -ln(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybstxkcafiar4eysf4c1qedjf3lntmv1ea.png)
We can now use the property shown below to make this into exponential form:
![Log_(a)b=x\\means\\a^x=b](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i3i0pmh8i6cbiofg3a6pniahv0igtx5kas.png)
So, we write:
![Log_(e)(2x) = -ln(2)\\e^(-ln(2))=2x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mol4t5h6z4yjpc18fs4qr57sqf4p0eja1g.png)
We recognize another property of exponentials:
![a^(bc)=(a^(b))^(c)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p63hmpc5eqechs943uacepic4mh6sxsak4.png)
So, we write:
![e^(-ln(2))=2x\\(e^(ln(2)))^(-1)=2x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/28vfj68wa7o9oznbi527phm97hj5joe1qw.png)
Also, another property of natural logarithms is:
![e^((ln(a)))=a](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ngpgz5svwp9pqd792t5joib9ce788w7wzh.png)
Now, we simplify:
![(e^(ln(2)))^(-1)=2x\\(2)^(-1)=2x\\(1)/(2)=2x\\x=((1)/(2))/(2)\\x=(1)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rqnnzlfktjz691uxdqioifpb2brhm7bsn6.png)
This is the answer.